COMMUNICATION TOOLS IN THE PROJECT TEAM (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The transition of society to an innovative economy encourages the search for an adequate management system in the context of project implementation. Effective communication encourages a successful solution to this problem. The purpose of the article is to identify the essence of communication in the project team, its components, as well as methods and tools used for messaging, to analyze traditional and modern methods of information exchange in the project team.The most desirable characteristics of a project team member identified: ability to cooperate with others, responsibility, loyalty to the project manager, ability to solve problems, commitment to the project, consistency and diligence.Established that the cooperation of the project team based on a clear division of responsibilities and effective communication between them. This is the responsibility of the project manager, who coordinates the work of the entire team and units involved in the project. The project manager performs a communicative function, as he acts as a mediator between the management of the organization and members of the project team. He must ensure the effective exchange of information in the team.Proved that in the process of communication the main elements go through a number of interrelated stages: the origin of the idea, coding and channel selection, converting an idea into a message, transmitting a message to the recipient, decoding, feedback. Noise sources can interfere with the exchange of information.The authors identified the consequences of inadequate flow of information in the project: misunderstanding of the message by the recipient, duplication of measures taken by project teams and their antagonistic directions, incorrect or late provision of information to project stakeholders.Substantiated that there is no single method of information exchange. Traditional meetings supported by electronic systems and visual communication. Telephone communication complemented by video conferencing systems, paper documentation by electronic means, and traditional whiteboards transformed into virtual ones. Computer communication systems allow you to exchange information faster and more efficiently. The project manager must adapt the communication tools to the project team taking into account the form, channel and time of communication; create clear rules for the transmission of specific messages in the project team.
Keywords: characteristics of the project team member, communicative function of the project manager, computer communication systems, inadequate information, methods of information exchange